Introduction: Symposium on Intellectual Property, Digital Technology & Electronic Commerce - Charles R. McManis (Washington University Journal of Law & Policy, 2002)
April 6-7, 2001, at the 2001 Heart of America Intellectual Property Conference, jointly sponsored by Washington University School of Law and the Bar Association of Metropolitan St. Louis, with the cooperation of the St. Louis Technology Gateway Alliance and Thompson Coburn, L.L.P. Three keynote speakers introduced the three major themes of the conference: Marybeth Peters, Register of Copyrights at the U.S. Copyright Office, spoke on digital copyright issues; Commissioner Mozelle Thompson of the Federal Trade Commission, spoke on the regulation of electronic commerce; and Stephen Kunin, Deputy Commissioner for Patent Examination Policy, U.S. Patent and Trademark Office, spoke on the eligibility of business software applications for patent protection. In keeping with these three themes, seven law professors and two economists each presented a paper on a personally selected topic. This volume includes these papers in addition to a related article. In total, three articles address digital copyright and database protection, four articles address the Uniform Computer Information Transactions Act (UCITA) and electronic commerce, and three articles focus on business method patents and bioinformatics.
Keywords: Intellectual property; Electronic commerce; Digital technology